Should Cytochrome P450 Inducers be Used to Accelerate Clearance of Brodifacoum from Poisoned Patients? - Israel Rubinstein; Richard van Breemen; Daniel G. Nosal; Guy Weinberg; Ronald C. Hershow; Douglas L. Feinstein (Adis, Springer Healthcare, 2019)
Abstract A recent multi-state outbreak of life-threatening bleeding following inhalation of synthetic cannabinoids has been attributed to contamination with the long-acting anticoagulant rodenticide (LAAR) brodifacoum, a second-generation, highly potent, long-acting derivative of the commonly used blood thinner warfarin. While long-term treatment with high-dose vitamin K1 restores coagulation, it does not affect brodifacoum metabolism or clearance, and, consequently, brodifacoum remains in the human body for several months, thereby predisposing to risk of bleeding recurrence and development of coagulation-independent injury in extrahepatic tissues and fetuses. This has prompted the evaluation of pharmacological measures that accelerate brodifacoum clearance from poisoned patients. Since the induction of certain cytochrome P450 (CYP) enzymes accelerates warfarin metabolism, using CYP inducers, such as phenobarbital, to accelerate brodifacoum clearance seems plausible. However, unlike warfarin, brodifacoum does not undergo significant metabolism in the liver, nor have the effects of phenobarbital on vitamin K1 metabolism been previously determined. In addition, the safety of phenobarbital in brodifacoum-poisoned patients has not been established. Therefore, we propose that CYP inducers should not be used to accelerate the clearance of brodifacoum from poisoned patients, but that alternative approaches such as reducing enterohepatic recirculation of brodifacoum, or using lipid emulsions to scavenge brodifacoum throughout the body, be considered.